SPQR : a history of ancient Rome - Beard, Mary (Profile Books, 2015)
Cicero's finest hour -- In the beginning -- The kings of Rome -- Rome's great leap forward -- A wider world -- New politics -- From empire to emperors -- The home front -- The transformations of Augustus -- Fourteen emperors -- The haves and have-nots -- Rome outside Rome.